The solution structure of a DNA*RNA duplex containing 5-propynyl U and C; comparison with 5-Me modifications. - Gyi, J; Gao, D; Conn, G; Trent, J; Brown, T; Lane, A (2003)
The addition of the propynyl group at the 5 position of pyrimidine nucleotides is highly stabilising. We have determined the thermodynamic stability of the DNA.RNA hybrid r(GAAGAGAAGC)*d(GC(p)U(p)U(p)C(p)U(p) C(p)U(p)U(p)C) where p is the propynyl group at the 5 position and compared it with that of the unmodified duplex and the effects of methyl substitutions. The incorporation of the propyne group at the 5 position gives rise to a very large stabilisation of the hybrid duplex compared with the analogous 5-Me modification. The duplexes have been characterised by gel electrophoresis and NMR spectroscopy, which indicate that methyl substitutions have a smaller influence on local and global conformation than the propynyl groups. The increased NMR spectral dispersion of the propyne-modified duplex allowed a larger number of experimental restraints to be measured. Restrained molecular dynamics in a fully solvated system showed that the propyne modification leads to substantial conformational rearrangements stabilising a more A-like structure. The propynyl groups occupy a large part of the major groove and make favourable van der Waals interactions with their nearest neighbours and the atoms of the rings. This enhanced overlap may account at least in part for the increased thermodynamic stability. Furthermore, the simulations show a spine of hydration in the major groove as well as in the minor groove involving the RNA hydroxyl groups.